Pulsed ultraviolet light decontamination of virus-laden airstreams. Issue 5 (4th May 2017) - Lin, William E.; Mubareka, Samira; Guo, Qiuquan; Steinhoff, Adam; Scott, James A.; Savory, Eric
ABSTRACT: Continuous ultraviolet germicidal irradiation (UVGI) has been extensively studied, but research on pulsed UVGI (PUVGI) is lacking and has primarily focused on disinfection of solid surfaces or liquids. This study addressed the gap in knowledge on the effectiveness of pulsed UVGI for disinfecting virus-laden calm air, with relevance to indoor rooms. Φ6 bacteriophage (a surrogate used to study communicable enveloped human respiratory viral pathogens such as influenza virus) was aerosolized by a Collison device into an enclosed test chamber, wherein the bioaerosol was exposed to PUVGI. The spectral content and performance of a pulsed white light lamp with a substantial UVC component were defined. Pulsed UV exposure of 10 to 30 s resulted in a two-log reduction in viable recovered virus from filter membranes and cyclone-based samplers. The small differences in Φ6 survival, after 10 to 30 s of exposure, emphasized the difficulty of complete eradication. However, exposure to 10 s of PUVGI resulted in significant reduction of virus viability. The dose–response displayed clear regimes of fast and slow exponential decay. Susceptibility factor for the fast-decay regime of aerosolized Φ6 ( Z = 0.24 m 2 /J) was similar to those reported for influenza A virus aerosols at similar relative humidity. Our study demonstrated the potency of PUVGI against a viral bioaerosol. This has potential implications for the control of infectious bioaerosols in the healthcare setting. © 2017 American Association for Aerosol Research